Evolution of C-V and I-V characteristics for a commercial 600 V GaN GIT power device under repetitive short-circuit tests. (September 2018) - Fu, J.Z.; Fouquet, F.; Kadi, M.; Dherbécourt, P.
Abstract: In this article, a repetitive and non-destructive short-circuit aging test is developed to characterize the electrical parameters evolutions of a 600 V GaN Gate Injection Transistor (GIT). The evolutions of C-V and I-V characteristics during the repetitive short-circuit tests with a relatively low bias voltage and long pulse duration are presented and summarized. The capacitance CGD at on-state mode and the gate current at relative high gate voltage show significant degradations before and after test.